Achievement profile of high school students on chemical dynamics material at three levels of representation. Issue 4 (February 2019) - Rakhmawan, A; Firman, H; Redjeki, S; Mulyani, S
Abstract: This study aims to explore information about the achievement profile of high school students on chemical dynamics material at three levels representation. This research uses non experimental design in the form of survey. Sample of the survey was 219 students of 11th grade high school students in Ketapang, West Borneo. Cluster random sampling was used as a sampling method. The data collection of survey use a multiple choice tests that contains chemical dynamics material that includes chemical kinetic concepts and chemical equilibrium concepts. Each item of the tests contains three levels representation such as macroscopic levels, symbolic levels, and submicroscopic levels. Based on the findings, it shows that high school students in Ketapang have high mean score of symbolic representation by 55, 1%, and sequentially 49, 8% in macroscopic level, and 40, 8% in submicroscopic level. The results based One Way ANOVA tests conclude that the mean score of each representation level was significantly different.